The round house : a novel - Erdrich, Louise (Harper, 2012)
When his mother, a tribal enrollment specialist living on a reservation in North Dakota, slips into an abyss of depression after being brutally attacked, 14-year-old Joe Coutz sets out with his three friends to find the person that destroyed his family.